The nexus between public communication and policy implementation revisited: insights from the Population and Civil Registration Service of South Sulawesi, Indonesia - Kondolele, Sukarniaty; Sultan, Muhammad Iqbal; Akbar, Muhammad; Putra, Bama Andika (Frontiers in Communication, 2025)
Effective public communication plays an essential role in ensuring government policies’ success. Taking the study case of the Population and Civil Registration Service of South Sulawesi Province, Indonesia, as the empirical case, this study validated the inter-relationship between the influential variables to public communication, which includes the role of actors, messages, media, and communicants. This study employs a quantitative method with a descriptive approach utilizing primary data obtained from questionnaires distributed to 61 service employees, policymakers, and the community as policy recipients between 2023 and 2024, and finds: (1) actors who have credibility and competence in conveying policy information play a significant role in increasing public understanding and acceptance of the policy; (2) the use of appropriate media, such as social media and face-to-face communication, proves effective in reaching and influencing communicants; (3) the effects of communication can be seen from the increase in public participation and awareness of population administration policies. To ensure greater success in policy implementation, government stakeholders need to adopt more targeted and interactive communication utilizing easily accessible media and ensuring the policy messages are delivered clearly. Optimizing public communication by strengthening the role of actors and using appropriate media is expected to increase the effectiveness of policy implementation at the Population and Civil Registration Service of South Sulawesi Province.